IMPLEMENTASI SURAT TELEGRAM PANGLIMA TNI NOMOR ST/398/2009 TENTANG PEMECATAN PRAJURIT TNI YANG TERLIBAT PENYALAHGUNAAN NARKOTIKA DIKAITKAN DENGAN NILAI – NILAI SAPTA MARGA, SUMPAH PRAJURIT DAN 8 WAJIB TNI - Wardana, R. Oki Ilham; Sudarto, Sudarto (LITERATUS, 2024)
The abuse of narcotics among the Indonesian National Armed Forces (TNI) personnel is a serious issue that can undermine the integrity and professionalism of the military. The Telegram Letter of the TNI Commander Number ST/398/2009 regarding the Dismissal of TNI Personnel Involved in Narcotics Abuse serves as a legal basis to address this problem. This study aims to analyze the implementation of the TNI Commander’s Telegram Letter Number ST/398/2009 in the dismissal of personnel involved in narcotics abuse, and its correlation with the values of the Sapta Marga, the Soldier’s Oath, and the 8 Obligations of TNI. This research uses a normative juridical approach with qualitative analysis, examining regulations, legal norms, and their application in the context of military discipline. The study findings indicate that the implementation of the TNI Commander’s Telegram Letter Number ST/398/2009 has been carried out fairly well, although there are still challenges in the enforcement of dismissals and discipline in the field. The values of Sapta Marga, the Soldier’s Oath, and the 8 Obligations of TNI are essential foundations in making dismissal decisions, as an effort to maintain the image and honor of the TNI.